Ethanol Extract of Sanguisorbae Radix Inhibits Mast Cell Degranulation and Suppresses 2,4-Dinitrochlorobenzene-Induced Atopic Dermatitis-Like Skin Lesions - Ju-Hye Yang; Jae-Myung Yoo; Won-Kyung Cho; Jin Yeul Ma (Mediators of Inflammation)
Sanguisorbae Radix (SR) is well known as herbal medicine named “Zi-Yu” in Korea, which is the dried roots of Sanguisorba officinalis L. (Rosacease). We investigated the underlying mechanism on the inhibition of atopic dermatitis (AD) of an ethanol extract of SR (ESR) using 2,4-dinitrochlorobenzene- (DNCB-) induced AD mice model. Oral administration of ESR significantly suppressed DNCB-induced AD-like symptoms such as scratching behavior, ear thickness, epidermal thickness, and IgE levels. To investigate the effects of ESR treatment on degranulation of IgE/Ag-activated mouse bone marrow-derived mast cells (BMMCs), we measured the release of β-hexosaminidase (β-HEX, degranulation marker). ESR decreased the infiltration of eosinophils and mast cells into the AD skin lesions. Furthermore, ESR significantly inhibited degranulation of IgE/Ag-activated BMMCs. We have demonstrated that ESR decreased AD symptoms in mice and inhibits degranulation of IgE/Ag-activated mast cells. Our study suggests that ESR may serve as a potential therapeutic candidate for the treatment of AD symptoms.